Carnal curiosity [large type] - Woods, Stuart (Woods, Stuart. Stone Barrington novel., 2014)
"Stone Barrington seems to have a knack for being in the wrong place at the wrong time. When Manhattan's elite are beset by a series of clever crimes -- and Stone is a material witness -- he and his former partner Dino Bacchetti find themselves drawn into the world of high-end security and fraud, where insider knowledge and access are limited to a privileged few, and the wealthy are made vulnerable by the very systems meant to keep them safe" --